Preclinical assessment of IRDye800CW‐labeled gastrin‐releasing peptide receptor‐targeting peptide for near infrared‐II imaging of brain malignancies - Yuan Zhang; Li Wang; Chengkai Zhang; Jingjing Zhang; Linhao Yuan; Shucheng Jin; Wenjianlong Zhou; Xiudong Guan; Peng Kang; Chuanbao Zhang; Jie Tian; Xiaoyuan Chen; et al. (Wiley, 2023)
Abstract We aimed to develop a new biocompatible gastrin‐releasing peptide receptor (GRPR) targeted optical probe, IRDye800‐RM26, for fluorescence image‐guided surgery (FGS) of brain malignancies in near‐infrared window II (NIR‐II) imaging. We developed a novel GRPR targeting probe using a nine‐amino‐acid bombesin antagonist analog RM26 combined with IRDye800CW, and explored the fluorescent probe according to optical properties. Fluorescence imaging characterization in NIR‐I/II region was performed in vitro and in vivo. Following simulated NIR‐II image‐guided surgery, we obtained time‐fluorescent intensity curves and time‐signal and background ratio curves. Further, we used histological sections of brain from tumor‐beating mice model to compare imaging specificity between 5‐aminolevulinic acid (5‐ALA) and IRDye800‐RM26, and evaluated biodistribution and biocompatibility. IRDye800‐RM26 had broad emission ranging from 800 to 1200 nm, showing considerable fluorescent intensity in NIR‐II region. High‐resolution NIR‐II imaging of IRDye800‐RM26 can enhance the advantages of NIR‐I imaging. Dynamic and real time fluorescence imaging in NIR‐II region showed that the probe can be used to treat brain malignancies in mice between 12 and 24 h post injection. Its specificity in targeting glioblastoma was superior to 5‐ALA. Biodistribution analysis indicated IRDye800‐RM26 excretion in the kidney and liver. Histological and blood test analyses did not reveal acute severe toxicities in mice treated with effective dose (40 μg) of the probe for NIR‐II imaging. Because of the considerable fluorescent intensity in NIR‐II region and high spatial resolution, biocompatible and excretable IRDye800‐RM26 holds great potentials for FGS, and is essential for translation into human use.